Phosphatidylinositol Synthase and Diacylglycerol Platforms Bust a Move - Bankaitis, Vytas A.; Grabon, Aby (Developmental cell, 2011)
Kim et al. (2011) challenge the dogma that phosphatidylinositol synthesis is restricted to the endoplasmic reticulum (ER) by showing that a mobile membrane compartment transports phosphatidylinositol synthase from the ER to numerous cellular compartments, including the plasma membrane. These findings significantly impact our view of phosphoinositide signaling in the cell.